The language of time a reader - Mani, Inderjeet.; Pustejovsky, J.; Gaizauskas, Robert. (Oxford University Press, 2005)
"This book includes selected classic and contemporary papers in four areas: tense, aspect and event structure; temporal reasoning; the temporal structure of natural language discourse; and temporal annotation. Introductions to each area provide technical background for the non-specialist, explaining the underlying connections across disciplines"--Provided by publisher.